Effects of a competitive season on the plasma lipid profile of soccer players - Marsigliante, S.; My, G.; Selmi, O.; Villani, E. P.; Hawani, A.; Muscella, A. (Physiological Reports, 2025)
This study aimed to evaluate the impact of a soccer season on the lipid profile of professional soccer players. Forty male players participated in the study. Blood samples for lipid profile analysis were collected at four time points: before the start of the training period (T0), immediately after the 4-week training phase (T1), at mid-season (T2, 23 weeks after T0), and the end of the season (T3, 43 weeks after T0). Throughout the competitive season, there was a significant decrease in body fat percentage (BFP, p < 0.001, RM-ANOVA) and an increase in fat-free mass (FFM, p < 0.001, RM-ANOVA). Plasma levels of total cholesterol (TC) and LDL cholesterol (LDL) significantly decreased (TC: p = 0.003, LDL: p = 0.033, RM-ANOVA), whereas HDL cholesterol (HDL) levels increased significantly in response to training (p = 0.013, RM-ANOVA). Triglyceride (TG) concentrations were significantly higher before the season than after (p < 0.001, RM-ANOVA). Additionally, the LDL/HDL and TC/HDL ratios showed significant reductions over the season (LDL/HDL: p = 0.004, TC/HDL: p < 0.001, RM-ANOVA). The observed decrease in LDL, TC, and TG levels, along with the increase in HDL levels at the end of the season. These results suggest that regular soccer training induces favorable changes in the lipid profile of professional players. Further studies are needed to determine whether such changes are associated with long-term health outcomes in elite athletes, particularly considering their typically low baseline risk for cardiovascular conditions.